PROGRAM INOVASI GERAKAN “BERINISIATIF (BERIKAN HANYA ASI EKSKLUSIF)” SEBAGAI UPAYA MEWUJUDKAN GENERASI EMAS BERKUALITAS - Brivian Florentis Yustanta; Dintya Ivantarina (STIKES dan AKZI Karya Husada Kediri, 2022)
All the essential nutrients required for survival, growth, development and immunological, antimicrobial, and anti-inflammatory factors in infants are obtained from breast milk during the first six months of life. However, the problem of not achieving exclusive breastfeeding coverage is still a major problem in infants beside the increase in infant mortality in the first six months of life. This is also a problem at the Mojoagung Health Center, especially in Dukuhdimoro village regarding the achievement of exclusive breastfeeding coverage from January - March 2022 which still does not meet the target of (-) 16.79%. This is due to the lack of knowledge of mothers since pregnancy and socialization from health cadres about exclusive breastfeeding. These problems require community service activities in the form of an innovation program in the form of the